A new monotypic genus of ant-mimicking Coraebini (Coleoptera: Buprestidae: Agrilinae ) from Madagascar - Bellamy, C. L. (Zootaxa, 2008)
Following the itemization of the described Madagascan Coraebini (Buprestidae: Agrilinae) (Bellamy 2001a), additional new genera and species of this large fauna have been described (Bellamy 2001b, 2003, 2006). After a preliminary study of the perceived ant-mimicking species I have accumulated in loans from, and during previous visits to, the vast collection of this fauna held by the Muséum national d’Histoire naturelle, Paris, a new monotypic myrmecomorphic genus and species is described. All other putative ant-mimicking species amongst previously described and currently available specimens belong to the genus Entomogaster Saunders, 1871. The new genus is described now for the one new species found to not be congeneric with Entomogaster. In deference to the classification for the tribe Coraebini Bedel, 1921 presented by Kubáň, et al. (2001), the genus-group taxon described herein is provisionally placed in the subtribe Toxoscelina Majer, in Kubáň, et al., 2001.